Rancang Bangun Sistem Absensi Siswa Berbasis Web Menggunakan Metode Waterfall Di MTS Arrahmaniyah - Darmawan, Dwiky; Letto Adoe, Gusti; Ramadhan, Wahyu; Saprudin (CV. Shofanah Media Berkah, 2024)
One of the most crucial elements of a school is student attendance, which demonstrates how focused and disciplined the students are in their studies. Manual attendance techniques are still used by many businesses, including MTS Arrahmaniyah. These procedures have a number of drawbacks, such as inaccurate recording, excessive paper use, and the possibility of data manipulation. This study uses the waterfall method to create a web-based attendance system in order to address these issues. Through the phases of requirements analysis, design, implementation, testing, and maintenance, the system can be created in an organized way thanks to the waterfall technique. The purpose of this system is to more precisely and effectively record attendance in real time. This solution provides clear data access for educators and school personnel. The Laravel framework, PHP, and MySQL are among the technologies utilized to construct this system. It is anticipated that the waterfall-method web-based attendance system will improve data administration, decrease paper usage, and boost MTS Arrahmaniyah's operational efficacy.